Is the distinction between inside money and outside money fruitful? - GAMBINO, A. (PSL Quarterly Review, 2014)
According to neo-classical theory money is neutral and monetary policy in the long run trivial, provided there is no rigidity in prices or incomes, no “money illusion” and that the elasticity of price expectation is not equal to unit. Conversely, according to Gurley and Shaw, the adoption of the distinction between inside and outside money would show that even if all the above conditions were realised, money would not be neutral if, as is true in real life, inside and outside money coexist. They maintain that monetary policy would be neutral only if, and insofar as, there were proportional changes in the quantity of the two types of money. According to the author, however, there appears to be no justification for maintaining that the distinction implies a new condition for the achievement of neutrality, and least of all should it be assumed that it destroys the usefulness of the neutrality of money theorem. JEL: E52, E40, E31